UJI KETAHANAN PADI LOKAL POTENSIAL ASAL BARAT-SELATAN ACEH TERHADAP PENYAKIT HAWAR DAUN BAKTERI - Wira Hadianto; Nana Ariska; Zainal Abidin (Universitas Teuku Umar, 2020)
Aceh Province has many local varieties that are still cultivated by farmers, especially in the South-West Region of Aceh, the local rice needs to be identified and used as a source of genes in the assembly of new improved varieties to support food security and sustainable agriculture. Bacterial leaf blight (HDB) is one of the limiting factors in rice production. HDB disease is caused by Xanthomonas oryzae pv. oryzae (Xoo), which can reduce rice yield by 30-40%. However, the potential of these varieties as sources of resistance genes against HDB has not been evaluated. This study aims to determine and obtain the potential genotypes of local rice in the West-South Region of Aceh that are resistant to Bacterial Leaves Disease. The research was carried out at the Experimental Garden of the Faculty of Agriculture, Teuku Umar University, Meulaboh, West Aceh from January to completion. The research was carried out starting from the treatment and seeding, preparation of planting media, planting, observation variables: Plant height and number of tillers per age 60 HST, incubation period and length of the observed lesio: 21 HSI: Test results of potential local rice resistance in the West- South Aceh obtained 9 genotypes that are resistant to bacterial leaf blight. The genotypes are used as genetic sources for assembling new high yielding varieties Keywords : Bacterial, Bacterial leaf blight, rice of local varieties,